SISTEM INFORMASI MANAJEMEN PENJUALAN GAS BERBASIS WEB PADA PANGKALAN GAS ADITAMA - Muhammad Riandy; Bambang Riono Arsad (Universitas Pancasila, 2025)
Pangkalan gas Aditama is a gas distribution center that currently still uses a manual system in running its business, where transaction records are still paper-based and customers must come directly to the store to purchase gas or inquire about gas stock information. This condition often leads to customer disappointment as they have to make multiple trips when the desired gas stock is depleted or the gas delivery truck has not arrived. Additionally, manual transaction recording makes data vulnerable to loss or damage. To address these issues, a web-based gas sales management information system was developed using Python programming language with Flask framework for back-end and front-end integration. This system is designed to allow customers to check gas stock without visiting the store, make online orders, and receive notifications about LPG 3 kg truck arrivals. The system development used the waterfall method with data collection through direct observation, owner interviews, and literature study. System testing conducted using the blackbox method showed that all features function properly, including gas stock information, truck arrival push notifications, online ordering with payment gateway, complaint management, product returns, and integrated sales reporting. The system can be accessed by five types of users with different access rights: guest, customer, admin, cashier, and warehouse staff. The result of this research is a management information system that helps meet user needs and improves operational efficiency at pangkalan gas Aditama.